Transformasi Modus Kejahatan Ekonomi Transnasional di Era Digital: Analisis Hukum Pidana dan Teknik Forensik Siber - Djunarjanto, Arief Agus; Purwati, Ani; Marina, Liza (SENTRI: Jurnal Riset Ilmiah, 2025)
The transformation of transnational economic crime in the digital era has fundamentally changed the way perpetrators commit crimes, presenting new challenges for criminal law enforcement. This study adopts a normative juridical approach, utilizing statutory analysis, case studies, and comparative law to examine the evolution of digital economic crimes and the strategic role of cyber forensics. Case studies such as money laundering through crypto assets using chain hopping techniques and Business Email Compromise (BEC) schemes reveal the complexity of cross-border jurisdiction, legal gaps in defining digital assets like cryptocurrency and NFTs, and evidentiary challenges in presenting digital proof in court. Cyber forensics, through techniques such as network forensics, malware analysis, and blockchain analysis, has proven crucial in collecting and validating digital evidence. However, law enforcement continues to face obstacles, including limited regulations, insufficient human resource capacity, and increasingly sophisticated anti-forensic techniques. This research recommends regulatory updates, enhanced training for law enforcement personnel, strengthened international cooperation, and public education to raise awareness of digital crime risks. Synergy between criminal law, forensic technology, and cross-border collaboration is essential for effectively combating digital economic crimes.